2022
DOI: 10.3390/ijms23105605
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Arranged Thermal Proximity Coaggregation (smarTPCA)—A Novel Approach to Characterize Protein–Protein Interactions in Living Cells by Similar Isothermal Dose–Responses

Abstract: Chemical biology and the application of small molecules has proven to be a potent perturbation strategy, especially for the functional elucidation of proteins, their networks, and regulators. In recent years, the cellular thermal shift assay (CETSA) and its proteome-wide extension, thermal proteome profiling (TPP), have proven to be effective tools for identifying interactions of small molecules with their target proteins, as well as off-targets in living cells. Here, we asked the question whether isothermal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Furthermore, TMT-DDA detected significant thermal stabilization of myosin light chain kinase (MYLK) (3.6 ± 0.6 °C) following treatment with losmapimod, but the protein was not detected in any DIA datasets (Figure S3A). A recent study reported MYLK to be a potentially new intracellular interaction partner of MAPK14, which may have been stabilized by association due to MAPK14 target engagement. Stability changes in proteins present in a complex have been identified previously with TPP, for example, kinase complexes containing cyclins were stabilized by the kinase inhibitor staurosporine .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TMT-DDA detected significant thermal stabilization of myosin light chain kinase (MYLK) (3.6 ± 0.6 °C) following treatment with losmapimod, but the protein was not detected in any DIA datasets (Figure S3A). A recent study reported MYLK to be a potentially new intracellular interaction partner of MAPK14, which may have been stabilized by association due to MAPK14 target engagement. Stability changes in proteins present in a complex have been identified previously with TPP, for example, kinase complexes containing cyclins were stabilized by the kinase inhibitor staurosporine .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TMT-DDA detected significant thermal stabilization of myosin light chain kinase (MYLK) (3.6 ± 0.6 °C) following treatment with losmapimod, but the protein was not detected in any DIA datasets (Figure S3A). A recent study reported MYLK to be a potentially new intracellular interaction partner of MAPK14, 55 which may have been stabilized by association due to MAPK14 target engagement.…”
Section: Performance For Target Deconvolutionmentioning
confidence: 99%
“…Furthermore, TMT-DDA detected significant thermal stabilisation of myosin light chain kinase (MYLK) (3.6 ± 0.6°C) following treatment with losmapimod, but the protein was not detected in any DIA datasets ( Figure S3A ). A recent study reported MYLK to be a potentially new intracellular interaction partner of MAPK14 52 , which may have been stabilised by association due to MAPK14 target engagement. Stability changes in proteins present in a complex have been identified previously with TPP, for example, kinase complexes containing cyclins were stabilized by the kinase inhibitor staurosporine.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal proteome pro ling with temperature range (TPP-TR) was essentially performed as described [17,34,86,92] employing 40 µM as nal bromoxib concentration and 30 min treatment time on live Ramos cells in three biological replicates (n = 3). In brief, aliquots of compound treated and control cells were shortly incubated side-by-side at ten discrete temperatures, equally distributed in a range between 37°C and 68.5°C, lysed, and the cell extracts containing the fraction of soluble, non-denatured proteins were obtained by centrifugation.…”
Section: Thermal Proteome Pro Ling (Tpp)mentioning
confidence: 99%